Toxicity, mutagenicity and stability assessment of simply produced electrolyzed water as a wound healing agent in vitro. (March 2021) - Reis, R; Sipahi, H; Dinc, O; Kavaz, T; Charehsaz, M; Dimoglo, A; Aydın, A
Over the last decade, electrolyzed water (EW) produced by salt and tap water has gained importance due to its antimicrobial effects. Regarding to chlorine-based compounds, EW also used in post-harvest safety of food processing and sterilization of surfaces. The latest studies suggested that EW might act as wound healing agent due to anti-infective and cell proliferative properties. In this study, we evaluated acute contact cytotoxicity in L929 mice fibroblast cells and wound healing activity of EWs in vitro. In addition, mutagenic activity was evaluated by Ames test with and without metabolic activation by S9 fraction and the stability profile of freshly prepared EWs has been followed up. According to the results, strong acid (StAEW) and mixed EW (MEW) showed dose-dependent cytotoxicity due to possible high HOCl concentration, while slightly acidic and catholyte EW (CEW) were not cytotoxic even applied directly for 30 sec. Further, StAEW and CEW showed a significant increase in L929 cell migration in scratch assay. Likewise, with/ without metabolic activation, neither of EWs had shown mutagenic profile in TA 98 and TA100 strains of Salmonella typhimurium. Follow-up of ORP (oxidation-reduction potential), pH and FCC (free chlorine concentration) showed that temperature and light were important storage conditions to maintain a stable profile particularly for ORP and FCC, which are the most important indicators for biological activity of EW. According to the present findings, it can be suggested that particularly StAEW, may represent a valuable wound healing agent with an achievable, economical and easy production system when stored under proper conditions.